Effect of platelet-rich fibrin on wound healing, adhesions, and hemostasis after inferior turbinoplasty surgery - Abdelhakim Fouad Ghallab; Mohamed Fahmy Shendy; Samer Badie Kamel; Mohamed Ali Adam; Mohamed Goda Elnems (The Egyptian Journal of Otolaryngology)
Abstract Background Inferior turbinate enlargement is a prevalent cause of chronic nasal obstruction, often requiring surgical intervention when medical treatment fails. Platelet-rich fibrin (PRF) has been reported to mitigate post-operative complications following nasal surgeries. This work aims to evaluate the efficacy of PRF on hemostasis, adhesions, crust formation, and mucosal healing post-turbinoplasty. Results Demographic characters showed no statistical differences in age (p = 0.62) or gender (p = 0.342), but the mean operative time was significantly shorter in the non-PRF group (22.80 ± 2.02) compared to the PRF group (p > 0.001). Early hemostasis and prevention of crustation were significantly better in the PRF group (p = 0.03 and p = 0.024, respectively). No significant difference was observed regarding adhesions between the groups (p = 1). Conclusion The PRF membrane is an affordable and easy method that acts as a protective layer, reducing crusting, ensuring hemostasis, promoting healing by shortening the period of recovery post inferior turbinoplasty and so improving the quality of life of the patients.